2009
DOI: 10.1080/15213260903287267
|View full text |Cite
|
Sign up to set email alerts
|

Virtually True: Children's Acquisition of False Memories in Virtual Reality

Abstract: Previous work on human memory has shown that prompting participants with false events and self-relevant information via different types of media such as narratives, edited 2-dimensional images, and mental imagery creates false memories. This study tested a new form of media for studying false memory formation: Immersive Virtual Environment Technology (IVET). Using this tool, we examined how memory was affected by viewing dynamic simulations of avatars performing novel actions. In the study, 55 preschool and el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
66
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
3
3

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(69 citation statements)
references
References 65 publications
2
66
0
1
Order By: Relevance
“…Source monitoring errors and false memories have been found in previous research relating to watching films (Roberts & Blades, 1999), narratives, and virtual worlds (Segovia & Bailenson, 2009). It could perhaps be speculated that since videogames can elicit emotions, memories can be enhanced that facilitate the occurrence of involuntary memories later on (Berntsen & Rubin, 2002).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Source monitoring errors and false memories have been found in previous research relating to watching films (Roberts & Blades, 1999), narratives, and virtual worlds (Segovia & Bailenson, 2009). It could perhaps be speculated that since videogames can elicit emotions, memories can be enhanced that facilitate the occurrence of involuntary memories later on (Berntsen & Rubin, 2002).…”
Section: Discussionmentioning
confidence: 98%
“…Studies have demonstrated that the playing of videogames can have both intended (Brown et al, 1997) and unintended effects (Anderson & Dill, 2000;Beullens, Roe, & Van den Bulck, 2008). Scholars had speculated that transfer effects may be more pronounced if virtual reality mechanisms become more realistic (e.g., Persky & Blascovich, 2008;Tamborini et al, 2004), and immersive (Segovia & Bailenson, 2009). According to Johnson, Hashtroudi and Lindsay (1993), memories from virtual experiences are similar to real world memories because they are rich in perceptual detail (e.g., visual and auditory cues) and that facilitate their recall.…”
Section: Introductionmentioning
confidence: 99%
“…Because imagination from the starting point of a graphical rendering may require less effort and attention than imagination from a blank slate, people may more easily imagine the future self when seeded with an image that is based on their present appearance (as the renderings in the experiment are). These studies were motivated, in part, by others who have used virtual reality as a tool (Blascovich and Bailenson 2011) for influencing: consumer behavior (Ahn and Bailenson, in press), health behavior (Fox and Bailenson 2009), financial decision making (Yee and Bailenson 2007), and memory (Segovia and Bailenson 2009). …”
Section: Age-progressed Embodiments Of the Future Selfmentioning
confidence: 99%
“…Thus, we cannot be sure whether the attractiveness effects observed in these studies are similar to the classic attractiveness effects observed with real people in the literature. Lastly, although some research has used avatar methodologies with children (see Segovia & Bailenson, 2009), we do not know whether children perceive avatars based on attractiveness in ways that match their perceptions of real peers.…”
mentioning
confidence: 99%